2023
DOI: 10.4155/tde-2022-0058
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil and nanocarrier-based Formulations Approaches for Vaginal Candidiasis

Abstract: An exclusive site for local drug delivery is the vagina, especially for vaginal infections. The fungus Candida albicans causes vaginal infection known as vulvovaginal candidiasis, a highly prevalent and recurrent gynaecological disease among women. Vaginal candidiasis affects over 75% of women at a certain point in their life and has a recurrence rate of 40–50%. Medicinal plants provide some very effective phytoconstituents which when delivered as nanosystems have enhanced therapeutic action and efficacy by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It is feasible to achieve the target-specific delivery of antifungals by appropriately ligand-tagging the formulation. This results in a lower required dosage, which in turn results in fewer adverse effects . According to existing literature, nanoformulations have the potential to exhibit a wide range of antifungal activity, facilitate sustained drug release, minimize the need for frequent dosing, and offer a novel mechanism of action that may help to surmount antibiotic resistance .…”
Section: Advantages Of Nanocarriers Over Conventional Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is feasible to achieve the target-specific delivery of antifungals by appropriately ligand-tagging the formulation. This results in a lower required dosage, which in turn results in fewer adverse effects . According to existing literature, nanoformulations have the potential to exhibit a wide range of antifungal activity, facilitate sustained drug release, minimize the need for frequent dosing, and offer a novel mechanism of action that may help to surmount antibiotic resistance .…”
Section: Advantages Of Nanocarriers Over Conventional Treatmentmentioning
confidence: 99%
“…This results in a lower required dosage, which in turn results in fewer adverse effects. 130 According to existing literature, nanoformulations have the potential to exhibit a wide range of antifungal activity, facilitate sustained drug release, minimize the need for frequent dosing, and offer a novel mechanism of action that may help to surmount antibiotic resistance. 131 El Rabey et al conducted a study wherein they observed that chitosan nanoparticles loaded with fluconazole exhibited inhibitory effects against C. albicans , C. parapsilosis , and C. glabrata , including drug-resistant strains.…”
Section: Advantages Of Nanocarriers Over Conventional Treatmentmentioning
confidence: 99%
“…Currently, there are several reviews available that discuss the research on antifungal nanosystems. Some researchers have summarized the application of nanosystems for the treatment of specific fungal infections [ 31 , 32 , 33 ]. Additionally, other scholars have introduced different types of nanosystems, such as metal-based, liposomal, and polymer-based systems, for antifungal therapy [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%